Energetics, migration and trapping of Zn interstitials in ZnO. (12th September 2019) - Azarov, Alexander; Kuznetsov, Andrej
Abstract: Zn interstitial (Zni ) is one of the fundamental intrinsic defects in ZnO and prominently affects the physical properties of the material. Here, the energetics and migration properties of Zni have been studied in ion implanted ZnO using a new approach based on the Li marker diffusion. Specifically, ZnO single crystals were implanted with 3.2 keV/amu B and BF2 ions and the release of Zni from the implanted regions during annealing was correlated with the advance of the characteristic Li depleted region into the bulk of the samples. Using this methodology, we calculate the activation energy of 1.45 eV to govern the process for B implants. Assuming that the migration energy of Zni to be of ~0.6 eV, as discussed previously in literature, a barrier for releasing Zni from the implanted region may be estimated as ~0.8–0.9 eV. Meanwhile, in the BF2 implanted samples, the migration of Zni is less efficient, as interpreted from the Li redistribution features in these samples; in particular, it is argued that Zni may be trapped by defect complexes related to the presence of F.